Effects study on the thermal stresses in a LEU metal foil annular target. (September 2015) - Govindarajan, Srisharan G.; Solbrekken, Gary L.
Abstract: The effects of fission gas pressure, uranium swelling and thermal contact conductance on the thermal–mechanical behavior of an annular target containing a low-enriched uranium foil (LEU) encapsulated in a nickel foil have been presented in this paper. The draw-plug assembly method is simulated to obtain the residual stresses, which are applied to the irradiation model as initial inputs, and the integrated assembly-irradiation process is simulated as an axisymmetric problem using the commercial finite element code Abaqus FEA. Parametric studies were performed on the LEU heat generation rate and the results indicate satisfactory irradiation performance of the annular target. The temperature and stress margins have been provided along with a discussion of the results. Highlights: Analyzed the thermal stresses in a low-enriched uranium foil based annular target. Included fission gas, uranium swelling, and thermal contact conductance effects. Worst case scenarios for temperature and stresses were found to be different. Sensitivity studies on the foil heat generation rates were performed. Temperature and stress were found to be within acceptable limits.